Use of Photogrammetry for Non-Disturbance Underwater Survey: An Analysis of In Situ Stone Anchors. Issue 1 (February 2016) - Fulton, Carrie; Viduka, Andrew; Hutchison, Andrew; Hollick, Joshua; Woods, Andrew; Sewell, David; Manning, Sturt
Abstract: Stone anchors comprise a significant portion of observable underwater cultural heritage in the Mediterranean and provide evidence for trade networks as early as the Bronze Age. Full documentation of these anchors, however, often requires their removal from their underwater environment, especially to calculate mass. We offer a methodology for using photogrammetry to record stone anchors still in situ and calculate their approximate mass. We compare measurements derived using measuring tapes with those derived using two different software programs for photogrammetric analysis, PhotoModeler Scanner (Eos Systems, Inc.) and PhotoScan Pro (Agisoft). First, we analyze stone anchors that had previously been removed from the underwater environment to establish a reference methodology. Next, we implement this methodology in an underwater survey off the southern coastline of Cyprus. Linear measurements for both programs correlate closely with those attained via measuring tape. The resulting estimates of volume of anchors in situ and on land are slightly greater using the photogrammetric methodology than the reference volumes obtained using a water displacement methodology. Overall, as an analytical tool, this methodology generates detailed surface information in minimal time underwater and preserves data for future analysis without necessitating the removal of the anchor from its underwater environment.